Relationship Level Of Community Knowledge About Covid-19 Vaccination On Covid-19 Events In Polonia Medan Puskesmas 2021-2022 - Heppy Jelita Sari Batubara (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to describe the distribution of characteristics of the people of Medan Polonia Village, to describe the public's knowledge about the COVID-19 vaccine, and to describe the public's knowledge about the importance of the COVID-19 vaccine at the Polonia Health Center, Medan Polonia District. cross sectional ie data collection is done only once on each respondent through a questionnaire as research data. The population in this study were all people who came to the Polonia Health Center to vaccinate against COVID 19. The sample in this study was the Medan Polonia District Community. The sampling technique in this study is total sampling. Total sampling is a sampling technique where the number of samples is the same as the population. Data processing is carried out in the following stages: Editing; coding; Data entry; Cleaning; Savings. the results of the research conducted at the Polonia Health Center regarding the Relationship between the Level of Public Knowledge About Vaccination against the Incidence of COVID-19 at the Polonia Health Center for the period February - March 2022, it was concluded that: the most common age group was the general public (18-49 years); the most common gender is female; the last education is high school; occupation, namely self-employed; personally exposed to COVID-19, i.e. never been exposed to as many as 79 people; personal COVID-19 vaccination, namely 88 people have been vaccinated; willing to be vaccinated as many as 102 people.